A PANS Method Based on Rotation-Corrected Energy Spectrum for Efficient Simulation of Rotating Flow - Liu, Benqing; Yang, Wei; Liu, Zhuqing (Frontiers in Energy Research, 2022)
A partially averaged Navier–Stokes method with a new expression of fk based on the rotation-corrected energy spectrum is proposed. It is coupled with the shear-stress transport turbulence model to simulate two typical rotating flows: rotating channel flow and flow in a centrifugal pump impeller. The results of two traditional energy spectrum-based fk expressions (ES1 and ES2) and DNS/experimental results are used for comparison. The results show that the fk distribution predicted based on the rotation-corrected energy spectrum is more reasonable. In the region with enhanced turbulence, more turbulence scales exist, such as the pressure side in the rotating channel flow, where the fk value is low and more turbulence scales are resolved. While in the region with suppressed turbulence, fewer turbulence scales exist, such as the suction side, where the fk value is relatively high. The model with a new fk expression can produce better results since it can give a more reasonable fk distribution. At the same time, the new model is more efficient since it shows better calculation performance with the same mesh scale and low cost with comparable calculation performance.